Familial Mediterranean fever (FMF) and beyond: a new horizon. Fourth International Congress on the Systemic Autoinflammatory Diseases held in Bethesda, USA, 6–10 November 2005. Issue 7 (10th April 2006) - Ozen, S; Hoffman, H M; Frenkel, J; Kastner, D
Abstract : Autoinflammatory diseases are characterised by seemingly unprovoked inflammation. They can be categorised as: hereditary (monogenic) autoinflammatory diseases, complex (polygenic/multifactorial) autoinflammatory diseases, and diseases where the course is affected by mutations in the defined autoinflammatory disease genes. Identification of the inflammatory pathways involved has opened up new areas of research which have implications for the treatment of these disorders and the pathogenesis of common inflammatory diseases.